BIMBINGAN KELOMPOK BERBASIS ONLINE DENGAN TEKNIK ROLE PLAY TERHADAP EFIKASI DIRI AKADEMIK SISWA - Asip Ibnu Sina; Euis Eti Rohaeti; Ardian Renata Manuardi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This study aims to find out online-based group guidance services with role play techniques on students' academic self-efficacy at MTs Al-Badar Gununghalu. This research is based on student problems that occur in schools. There are some students with low academic self-efficacy. The method used in this research is descriptive qualitative method. The type of approach used is a descriptive approach. Data collection techniques used in this study are interviews and observation. The subjects in the study were 1 teacher of counseling and 6 students who had low academic self-efficacy. Students who have low academic self-efficacy will affect their learning process. This may affect students to be lazy to study, high anxiety in doing assignments, low self-efficacy towards learning, and a sense of giving up quickly on learning. students are quite effective in overcoming students' academic self-efficacy problems, because it has a significant positive impact on students' academic self-efficacy.Keywords: : Group Guidance, Role Play, Academic Self-Efficacy